Gastrointestinal Symptoms in Children and Adolescents With Neurofibromatosis Type 1. Issue 6 (June 2018) - Ejerskov, Cecilie; Krogh, Klaus; Ostergaard, John R.; Joensson, Iben; Haagerup, Annette
ABSTRACT: Objectives: Neurofibromatosis type 1 (NF1) is a complex genetic disorder characterized by symptoms of the skin and nervous system. A previous study indicated that constipation is common in children with NF1. The aim of the present study was to investigate the phenotype and prevalence of gastrointestinal (GI) symptoms in a population of 4 to 17-year-olds with NF1 compared with their unaffected siblings. Methods: GI symptoms were assessed with a web-based, parent or self-administered, validated, Rome III diagnostic questionnaire. Participants were recruited from 1 of 2 Danish National Centers of Expertise for NF1. Logistic regression was used to estimate the prevalence of functional dyspepsia, irritable bowel syndrome (IBS), and constipation in each group and the groups were compared using odds ratio (OR). Results: We compared 102 NF1 patients (median age 10.3 years) and 46 of their unaffected siblings (median age 10 years). The overall likelihood of having GI symptoms usually attributed to either functional dyspepsia, IBS, or constipation was 30.4% in patients versus 10.9% in siblings, OR 3.58 (95% confidence interval 1.30 to 9.79). The prevalence of constipation was 22.5% in patients and 4.3% in siblings, OR 6.41 (95% confidence interval 1.45 to 28.24). The use of laxatives was 16% (n = 16) in patients and 2% (n = 1) in siblings. Conclusions: Overall, GI symptoms attributed to functional dyspepsia, IBS or constipation are more common in 4 to 17-year-olds with NF1 when compared with their unaffected siblings. The high prevalence indicates that GI dysfunction in NF1 is not functional but may be part of the underlying NF1 disorder. Abstract : Supplemental Digital Content is available in the text